A longitudinal study of multiple water source use in Bekasi, Indonesia: implications for monitoring safely-managed services. (18th October 2022) - Priadi, Cindy R.; Putri, Gita L.; Jannah, Qanza N.; Maryati, Sri; Afriana, Anita; Pratama, Mochamad Adhiraga; Foster, Tim; Willetts, Juliet
Abstract: Limited piped water services in low- and middle-income countries (LMICs) are likely to increase the use of multiple water sources, impacting access to safely managed water. The aim of this study was to analyze monthly variations of households' water source preferences in three subdistricts in Bekasi, adjacent to the capital city of Indonesia, through a monthly telephone survey of 87 households during 12 months. Households with 1, 2, and 3–4 drinking water sources formed 70, 27, and 3% of the 755 total responses, respectively. Of the 53 households that completed at least 11 of the 12 monthly surveys, around 32% of households resorted to other water sources as a complement for drinking water and other domestic purposes. Households switched from borehole water to bottled water for their primary drinking water in the wet season but still used borehole water as their complementary source. Unimproved source use as primary drinking water also increased during the wet season from 6 to 8%. Monitoring and risk assessment of water sources need to consider the use of multiple water sources while balancing out the limited resources to protect the population, especially the vulnerable, from unacceptable health risks. HIGHLIGHTS: At any given time, 30% of households had multiple drinking water sources. For all water use, multiple water sources increased to 74%. Borehole water use decreased by 6% during the wet season replaced by bottled water. Primary drinking water from an unimproved source at 2%, higher during the wet season. Use of unimproved sources as overall drinking water tripled, at 20%. Graphical Abstract